Analisa Dan Perancangan Sistem Informasi Produksi (SiPro) PT. UPAP - Hersatoto Listiyono; Anisa Istiqomah; P Purwatiningtyas; Zuly Budiarso (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2024)
PT UPAP is a company engaged in printing services, more precisely screen printing or screen printing, printing services are often needed by textile garment. Until now, PT UPAP has had approximately 70 garments spread across the provinces of Central Java, West Java, Jabodetabek and DIY. The existing system at PT UPAP is still done manually, starting from customer data collection, production, approval, product quality control, production stock data collection, recap data collection of production quality control reports , production stock reports to storage of other data, so that it is possible that during the process there are errors in recording the inaccurate reports made and delay in searching for the necessary data. The design of this information system is the best solution to solve the problems that exist in this company, in order to achieve an effective and efficient activity in supporting activities in this company.